(untitled) (The Strategic Review for Southern Africa, 2020)
Drawing on extended ethnographic fieldwork in the Islamic Republic of Mauritania (between 2001 and 2012), this article investigates how the intensifying regional insecurity is perceived and (re)acted upon by people inhabiting the frontier provinces of south-eastern Mauritania. It is argued that armed insurgencies and the emergence of nebulous assemblages such as the AQIM (Al-Qaeda Organisation in the Islamic Maghreb), must be analysed as constitutive elements in a complex convergent crisis which is currently undermining local livelihoods in multiple ways. In Mauritania and much of the Saharan and Sahelian regions, crisis has become chronic, and while people exhibit tremendous capacities to anticipate the uncertain and navigate a disequilibrated natural and political environment in general, a new kind of protracted fear is spreading. This article establishes how the AQIM is enacted locally as a phantom menace, which asserts itself through a form of omnipresent fear, nurtured by an inherent opaqueness. As this fundamental fear progressively permeates the nomadic landscape, it engenders a recasting of mobile strategies among the nomadic pastoralist groups who inhabit the interstitial desert spaces.